Cover Crops and Mechanical Scarification in the Yield and Industrial Quality of Upland Rice - Nascimento, Vagner do; Arf, Orivaldo; Alves, Marlene Cristina; Souza, Epitácio José de; Silva, Paulo Ricardo Teodoro da; Kaneko, Flávio Hiroshi; Teixeira Filho, Marcelo Carvalho Minhoto; Jalal, Arshad; Oliveira, Carlos Eduardo da Silva; Sabundjian, Michelle Traete; Ferrari, Samuel; Prado, Evandro Pereira; et al. (Frontiers in Environmental Science, 2022)
Mechanical soil scarification and cover crops cultivation are promising tools to minimize surface soil layer compaction in no-tillage systems. The objective of the current study was to evaluate the effects of mechanical soil scarification associated with predecessor and successive growth of cover crops on grain yield and industrial quality of upland rice in a no-tillage system. The research was carried out in randomized block design in a 5 x 2 factorial scheme with four replications in a Rhodic Haplustox soil with a clayey texture. The treatments consisted of five cover crops (Cajanus cajan, Crotalaria juncea, Urochloa ruziziensis, Pennisetum glaucum and fallow) andmechanical soil scarification (without and with). The fallow and C. cajan as a cover crop in mechanical soil scarification increased number of panicles plant-1 while cultivation of C. cajan, P. glaucum and C. juncea as covers crop in without scarification increased number of grains panicle-1, total number of grains panicle-1 and filled grains. Rice milling yield was increased in mechanical soil scarification regardless of the cover crop as well as scarification, and C. cajan as covers crop has increased grain yield of upland rice.